Vitamin E Does not Favor Recovery After Exercises: Systematic Review and Meta-analysis - de Lima, Katieli Santos; Schuch, Felipe; Righi, Natiele Camponogara; Neto, Léo José Rubin; Nunes, Guilherme Silva; Puntel, Gustavo; Chagas, Patrícia; da Silva, Antonio Marcos Vargas; Signori, Luis Ulisses (International Journal of Sports Medicine, 2024)
This review aimed to verify the effects of vitamin E supplementation on oxidative stress, inflammatory response, muscle damage, soreness, and strength in healthy adults after exercise. We searched the MEDLINE, EMBASE, SPORTDiscus, Cochrane CENTRAL, and Web of Science from inception to August 2023, with no language restrictions. We included randomized placebo-controlled trials evaluating the supplementation of vitamin E on the abovementioned outcomes after a bout of physical exercise in healthy participants (no restriction for publication year or language). Meta-analyses were conducted to compare vitamin E and placebo supplementations to obtain a 95% confidence interval (95%IC). Twenty studies were included (n=298 participants). The effect of supplementation was assessed between 0 h and 96 h after the exercise. Compared to placebo, vitamin E had no effects on lipid (95%IC= –0.09 to 0.42), protein (–2.44 to 3.11), SOD (–1.05 to 0.23), interleukin-6 (–0.18 to 1.16), creatine kinase (–0.33 to 0.27), muscle soreness (–1.92 to 0.69), and muscle strength (–1.07 to 0.34). Heterogeneity for the analyses on carbonyls, interleukin-6 (1 h and 3 h), and muscle soreness ranged between 70 to 94%. Supplementing with vitamin E should not be recommended to support the recovery process in healthy individuals after exercise, given the lack of efficacy in the analyzed variables following an exercise session.
Keywords: physical exercise; antioxidants; alpha-tocopherol